Perkembangan Historiografi Lingkungan di Indonesia - Ahmad Sholehuddin Suryanullah (UIN Imam Bonjol Padang, 2024)
The environmentalist movement in America in the 1970s and the EDEN (Ecology, Demography, and Economy in the Archipelago) project led by Peter Boomgaard triggered the emergence of environmental historiography in Indonesia. This article attempts to explain the development of environmental historiography in Indonesia from 1992-2023. By carrying out in-depth reading (bibliographical research) regarding the historiography that has been produced. This article shows that environmental historiography in Indonesia is experiencing development, starting from foreign writers, until shifting to Indonesian writers. The focus of the study, which was initially simple, became very complex, namely colonial exploitation which had an impact on environmental change, to the study of environmental conservation, environmental pollution, disasters, and the environmental movement.